The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.inorgchem.1c01370
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Active Sites and a Multiple-Micropore System for a Metal–Organic Framework Exhibiting High Separation of CO2/CH4 and C2H2/CH4

Abstract: Efficient gas separation and purification play a vital role in the current advanced development of industry, and the application of MOF adsorbents in this area with highly technical materials shows obvious advantages. On the basis of reticular chemistry, the 4-c lvt MOF adsorbent [CuDTTA]·3DMF·CH3CN has been constructed (CuDTTA; H2DTTA = 2,5-bis­(1H-1,2,4-triazol-1-yl)­terephthalic acid). CuDTTA reveals a multiple-micropore system and high-density active sites decorated on the channel surfaces, which are condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The simulated adsorption selectivities ( S ads ) for the 50/50 C 2 H 2 /CH 4 , C 2 H 4 /CH 4 , and C 2 H 6 /CH 4 binary equimolar mixtures are 332, 76, and 89, respectively. Exactly as in Figure b, in particular, the S ads (C 2 H 2 /CH 4 of 332) of MOF 2 at 298 K, close to that of ZJU-198a (391), has exceeded those observed in other MOFs such as Zr-SDBA (230), NbU-11 (175), CuDTTA (166), UTSA-50 (68), and PCM-48 (<25) as shown in Figure a. ,,,, These results indicate the potential adsorbent in the practical petroleum industry for C 2 /C 1 light hydrocarbon separation. Beyond that, the simulated adsorption selectivities of C 2 H 2 /C 2 H 4 and C 2 H 2 /C 2 H 6 are 3.9 and 2.2, respectively, where the pore size effect and similar polarizability lead to co-adsorption of C 2 H 2 with C 2 H 6 and C 2 H 4 …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The simulated adsorption selectivities ( S ads ) for the 50/50 C 2 H 2 /CH 4 , C 2 H 4 /CH 4 , and C 2 H 6 /CH 4 binary equimolar mixtures are 332, 76, and 89, respectively. Exactly as in Figure b, in particular, the S ads (C 2 H 2 /CH 4 of 332) of MOF 2 at 298 K, close to that of ZJU-198a (391), has exceeded those observed in other MOFs such as Zr-SDBA (230), NbU-11 (175), CuDTTA (166), UTSA-50 (68), and PCM-48 (<25) as shown in Figure a. ,,,, These results indicate the potential adsorbent in the practical petroleum industry for C 2 /C 1 light hydrocarbon separation. Beyond that, the simulated adsorption selectivities of C 2 H 2 /C 2 H 4 and C 2 H 2 /C 2 H 6 are 3.9 and 2.2, respectively, where the pore size effect and similar polarizability lead to co-adsorption of C 2 H 2 with C 2 H 6 and C 2 H 4 …”
Section: Resultsmentioning
confidence: 67%
“…The simulated adsorption selectivities (S ads ) for the 50/50 C 2 H 2 / CH 4 , C 2 H 4 /CH 4 , and C 2 H 6 /CH 4 binary equimolar mixtures are 332, 76, and 89, respectively. Exactly as in Figure 5b, in particular, the S ads (C 2 H 2 /CH 4 of 332) of MOF 2 at 298 K, close to that of ZJU-198a 47 (391), has exceeded those observed in other MOFs such as Zr-SDBA 48 (230), NbU- 11 49 (175), CuDTTA 50 (166), UTSA-50 51 (68), and PCM-48 52 (<25) as shown in Figure 6a. 1,35,56,58,59 53 In addition, the CO 2 loadings reached ∼1.6 mmol g −1 and the selectivity of the C 2 H 2 /CO 2 binary combinations is 5.7, while encouragingly, that of CO 2 /CH 4 (31) is higher than those of Ni-MOF-74 54 (29), SNNU-14 9 (19), FJU-44a 55 (16), JLU-Liu66 56 (9.4), and NOTT-125 57 (4.8), which promotes MOF 2 as a hopeful CO 2 adsorbent from depurinating biogas and flue gas mixtures (Figure 6b).…”
Section: Gas Adsorption Of Mof 1 and Mofmentioning
confidence: 59%
“…2c). The C 2 H 2 loading at 273 K is comparable to those of SNNU-150-Sc (68.2 cm 3 g −1 ) 48 and JLU-MOF66 (65.5 cm 3 g −1 ); 49 however, it is lower than those of SNNC-5-Sc (211.2 cm 3 g −1 ), 48 CuDTTA (102 cm 3 g −1 ), 50 and [Co 3 (tib) 2 (abdc) 2 (ox)] 2 •6H 2 O (94.5 cm 3 g −1 ). 51 The adsorption capacity of CO 2 at 273 K is comparable to that of SNNU-150-Sc (45.1 cm 3 g −1 ), 48 SNNU-34 (53.0 cm 3 g −1 ), 52 and [Cu(SiF 6 )(sdi) 2 ] (45.1 cm 3 g −1 ).…”
Section: Sorption Propertiesmentioning
confidence: 75%
“…Notably, among the polymers, polymer 1 shows the best sorption selectivity of CO 2 over N 2 at 273.15 K. Although this value is much lower than those of PVA/PAA-C 3 H 7 (341), 67 PVAm/PZEA-Pro/PZEA-Sar (210), 68 MPC-500 (140), 69 PIP-CMC/TMC (119), 70 and PIM-PI-1 (57.2), 71 the CO 2 /N 2 value of polymer 1 is comparable or exceeds those of CTFs (14.2–20.3), 72 PPFs (14.5–15.4), 73 MF-168-600 (16), 74 and PIM-1 S A / S B (12.7) 75 at 273.15 K and HC PPO-Br (20), 76 CCP-6 (17), 77 UiO-66 (16.7), 78 Sg (9.9), 79 and SBL-MIP-C-800 (9.5) 80 at 298.15 K. Likewise, the data collected in Table 3 show that the CO 2 /CH 4 sorption selectivities are theoretically predicted to be about 41.84, 40.22, and 35.08 at 273.15 K and 35.98, 36.14, and 33.64 at 298.15 K for polymer 1 to polymer 3 , respectively. Notably, polymer 1 among these polymers exhibits the highest gas adsorption selectivity of CO 2 over CH 4 at 273.15 K, which is superior to those of Tg-AzoCOF (37), 81 NGA (21.4), 82 MOPI-6-0.5 (18), 83 BOP-1 (5.48), 84 and NPC-1 (3.8) 85 at 273.15 K, and S-D-1.6 (34), 86 CuDTTA (29), 87 PIM-Cardo-TOT (25.5), 88 Cu-1 (9), 89 and Ni-MOF (2.9) 90 at 298.15 K. In addition, it should be particularly pointed out that the selective uptake of CO 2 over N 2 and CH 4 is mainly induced by the strong dipole–quadrupole interaction between the structurally accessible polar functional groups, heteroatoms and CO 2 molecules as well as the quadrupole–quadrupole interactions among the CO 2 molecules.…”
Section: Resultsmentioning
confidence: 94%
“…performance of porous organic polymers in practical gas adsorptive separation applications. Single-component physisorption isotherms for CO 2 , N 2 and CH 4 were systematically analyzed via volumetric methods at 273.15 K and 298.15 K, and the CO 2 /N 2 and CO 2 /CH 4 gas pairs were comprehensively calculated by employing the initial slope ratios from Henry's law constants of the pure gas adsorption isotherms at the same temperature and low-pressure coverage of less than 0.3 bar, as PVAm/PZEA-Pro/PZEA-Sar (210), 68 MPC-500 (140), 69 PIP-CMC/ TMC (119), 70 and PIM-PI-1 (57.2), 71 the CO 2 /N 2 value of polymer 1 is comparable or exceeds those of CTFs (14.2-20.3), 72 PPFs (14.5-15.4), 73 MF-168-600 ( 16), 74 and PIM-1 S A /S B (12.7) 75 at 273.15 K and HC PPO-Br (20), 76 CCP-6 ( 17), 77 UiO-66 (16.7), 78 Sg (9.9), 79 and SBL-MIP-C-800 (9.5) 29), 87 PIM-Cardo-TOT (25.5), 88 Cu-1 (9), 89 and Ni-MOF (2.9) 90 at 298.15 K. In addition, it should be particularly pointed out that the selective uptake of CO 2 over N 2 and CH 4 is mainly induced by the strong dipole-quadrupole interaction between the structurally accessible polar functional groups, heteroatoms and CO 2 molecules as well as the quadrupole-quadrupole interactions among the CO 2 molecules. On account of the systematic studies above, it has been demonstrated that the utilized carbonates are a family of lowcost and accessible candidates for preparing novel and highly porous hyper-cross-linked polymers possessing hierarchical architectures, versatile functionalities, enhanced gas uptake capacities and adsorption selectivities.…”
Section: Resultsmentioning
confidence: 99%